Microstructural lateralization of thalamocortical connections in individuals with a history of reading difficulties - Yueye Zhao; Jianyi Liu; Xue'er Ma; Zi-Gang Huang; Jingjing Zhao (NeuroImage)
Previous research has shown that the thalamus is crucial in reading, with its function depending largely on its connections with the cortex. However, the relationship between the lateralization of thalamocortical connections and reading has not been well-explored. This study investigates the microstructure and its lateralization differences in thalamocortical white matter fiber tracts in individuals with varying reading abilities and explores their relationship with reading skills and early reading performances. The study involved 26 Mandarin-speaking adults with a history of reading difficulties and 35 typically developing Mandarin-speaking adults. Severity of reading difficulties were accessed via the Chinese Adult Reading History Questionnaire (C-ARHQ) self-reported by participants. Reading-related abilities including reading accuracy, phonological awareness, and rapid automatized naming were assessed. Neuroimaging data, including T1-weighted and diffusion-weighted images, were collected. Thalamocortical white matter fiber tracts were reconstructed using the constrained spherical deconvolution (CSD) model and grouped into six regions based on connections with bilateral brain areas. The Neurite Orientation Dispersion and Density Imaging (NODDI) model was employed to evaluate the microstructural properties of these tracts, calculating lateralization indices for the orientation dispersion index (ODI), neurite density index (NDI), and isotropic volume fraction (VISO). Results revealed that individuals with reading difficulties had significantly lower NDI values in the left and right frontal-thalamic and occipital-thalamic fiber tracts compared to good readers. Additionally, greater rightward lateralization of frontal-thalamic white matter fiber tracts was linked to poorer early reading performance in those with reading difficulties. Our study reveals atypical thalamocortical white matter connections in adults with a history of reading difficulties, and the lateralization of these connections is influenced by severity of early reading difficulties.